2023
DOI: 10.3390/medicina59050918
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Accuracy of Three Electronic Apex Locators Using Different Sodium Hypochlorite Concentrations

Abstract: Background and Objectives: The aim of this study was to compare the accuracy of three types of electronic apex locators (EALs) when two different concentrations of NaOCl irrigation solutions are used by two operators. Materials and Methods: After creating the access cavities for 20 single rooted extracted teeth, the actual canal length (ACL) of each canal was determined visually using a #10 file and magnification. The teeth were subsequently inserted in plastic molds filled with alginate. The electronic measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Studies evaluating the accuracy of EALs in the presence of root canal irrigation solutions in permanent molars have produced varying findings. Some studies have determined that irrigation solutions do not affect the accuracy of EALs [22,23], while others have reported that irrigation solutions may cause short or long measurements [20,25]. This is the first study to evaluate the accuracy of an EAL in resorption primary teeth in the presence of NaOCl.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies evaluating the accuracy of EALs in the presence of root canal irrigation solutions in permanent molars have produced varying findings. Some studies have determined that irrigation solutions do not affect the accuracy of EALs [22,23], while others have reported that irrigation solutions may cause short or long measurements [20,25]. This is the first study to evaluate the accuracy of an EAL in resorption primary teeth in the presence of NaOCl.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported in some studies that modern EALs can maintain their accuracy in the presence of irrigation solutions [22,23]. Some authors argue that the presence of electrolyte solutions in the root canal is one of the most important factors affecting measurements made using EALs.…”
Section: Discussionmentioning
confidence: 99%
“…The use of double stoppers was intended to reduce potential errors from movement while measuring file length [8,9,17]. All measurements were taken twice [9,22,23]. Following this protocol, a total of 450 readings were obtained: 150 recordings to determine the actual length and 300 measurements acquired by the Root ZX.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Root ZX with K-file size 8 since this size provided significantly higher accuracy compared to size 15 [9]. The use of 5% NaOCl should not have affected our results since the accuracy of Root ZX was not affected by the different concentrations of NaOCl [22,24]. Overall, rigorous efforts were implemented to standardize and control potential factors that could impact the results of the current study.…”
Section: Discussionmentioning
confidence: 99%